2008
DOI: 10.1111/j.1747-0285.2008.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues in PEPHC1 Important for Binding to the Tumor‐Specific Receptor EGFRvIII

Abstract: EGFRvIII is a cancer-specific epidermal growth factor tyrosine kinase receptor mutation, expressed in different kinds of cancer, in particular ovarian, glioblastomas, and breast cancer. A peptide, PEPHC1, has previously been shown to bind selectively to EGFRvIII. An alanine scan was performed to identify the amino acid residues important for binding of PEPHC1 to EGFRvIII. The results indicate that the amino acid residues at the N-terminus of PEPHC1 are essential for the binding to the mutated receptor. One ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As previously mentioned, we have reported an alanine scan of PEPHC1 to identify the amino acid residues important for binding to EGFRvIII 17. Our results indicated that the amino acid residues at the N‐terminus of PEPHC1 are essential for the binding to the mutated receptor.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…As previously mentioned, we have reported an alanine scan of PEPHC1 to identify the amino acid residues important for binding to EGFRvIII 17. Our results indicated that the amino acid residues at the N‐terminus of PEPHC1 are essential for the binding to the mutated receptor.…”
Section: Resultssupporting
confidence: 57%
“…PEPHC1 had binding ability and selectivity to EGFRvIII. Very recently, we identified the amino acid residues in PEPHC1 important for binding to the tumor‐specific receptor EGFRvIII 17. Our results indicated that the amino acid residues at the N‐terminus of PEPHC1 are essential for the binding to the mutated receptor.…”
Section: Introductionmentioning
confidence: 78%
“…Thus, EGFRvIII is a promising marker for sensitive glioblastoma detection and localization in molecular MR imaging. PEPHC1 (the sequence: HFLIIGFMRRAACGA) is a small peptide that has been identified for specific binding with EGFRvIII [26]. Thus PEPHC1 grafting to PEGylated SPIONs could help to construct a targeted nanoprobe for sensitive characterization and detection of glioblastoma.…”
Section: Introductionmentioning
confidence: 99%